Flexible Cuprous Triazolate Frameworks as Highly Stable and Efficient Electrocatalysts for CO2 Reduction with Tunable C2H4/CH4 Selectivity. Issue 28 (24th May 2022) - Zhuo, Lin‐Ling; Chen, Pin; Zheng, Kai; Zhang, Xue‐Wen; Wu, Jun‐Xi; Lin, Duo‐Yu; Liu, Si‐Yang; Wang, Zhi‐Shuo; Liu, Jin‐Yu; Zhou, Dong‐Dong; Zhang, Jie‐Peng
Abstract: Cu‐based metal–organic frameworks have attracted much attention for electrocatalytic CO2 reduction, but they are generally instable and difficult to control the product selectivity. We report flexible Cu(I) triazolate frameworks as efficient, stable, and tunable electrocatalysts for CO2 reduction to C2 H4 /CH4 . By changing the size of ligand side groups, the C2 H4 /CH4 selectivity ratio can be gradually tuned and inversed from 11.8 : 1 to 1 : 2.6, giving C2 H4, CH4, and hydrocarbon selectivities up to 51 %, 56 %, and 77 %, respectively. After long‐term electrocatalysis, they can retain the structures/morphologies without formation of Cu‐based inorganic species. Computational simulations showed that the coordination geometry of Cu(I) changed from triangular to tetrahedral to bind the reaction intermediates, and two adjacent Cu(I) cooperated for C−C coupling to form C2 H4 . Importantly, the ligand side groups controlled the catalyst flexibility by the steric hindrance mechanism, and the C2 H4 pathway is more sensitive than the CH4 one. Abstract : Flexible Cu(I) triazolate frameworks functionalized with dinuclear copper sites can serve as highly stable and efficient electrocatalysts for CO2 reduction to C2 H4 /CH4, and the selectivity is tunable by the size of uncoordinated ligand side groups.